Efficiencies of finger joint of Light Red Meranti (experimental work) / Arshad Jamaluddin - Jamaluddin, Arshad (1996)
Finger Joint was developed to minimize wasting of wood in jointing. Generally, finger joint is use in glue laminated timber to increase the length of the structure without wasting too much of wood. The commercial finger joint for furniture industrial widely used. In this study, investigation on the suitability of Light Red Meranti to be jointed by using mini finger joint with the PRF glue through the samples. The primary objective of this study is to find the most effective profile from the five different commercial sizes that has been chosen which carry the highest tensile strength. This study employs samples of 20 x 30 x 600 mm in dimensions. These samples are glued at the middle using finger joint represent the actual structural members carrying tension load. A theoretical discussion of finger joint is also presented to analyze the data in order to achieve the objectives. The data showed conclusively that an adequately large glue-joint area to develop high shear resistance, as well as thin finger tips, are required to obtain maximum joint strength.